PENGARUH BAHASA DAERAH TERHADAP POLA KOMUNIKASI MAHASISWA FAKULTAS SASTRA UNIVERSITAS MUSLIM INDONESIA - Rahmat Rahmat; Umar Mansyur (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
The Influence of Regional Language on Communication Patterns of Students of the Faculty of Letters, Muslim University of Indonesia. This study aims to examine the description of regional language and its effect on student communication patterns. This type of research is quantitative research with regression techniques using a questionnaire instrument. The research data was sourced from students of the 2019 Indonesian Language and Literature Study Program. The number of samples was 59 people using descriptive statistical data analysis techniques and inferential statistics. The results showed that the local language had a significant influence on student communication patterns.